Beyond Pearl Harbor : A Pacific History - Farber, David, 1956-; Bailey, Beth L., 1957- (Book collections on Project MUSE., 2019)
"Many Americans have no idea that Pearl Harbor was not Japan's sole target, or that Japan's coordinated attacks hit the imperial possessions of western nations scattered across the broad reach of the Pacific Ocean. In this collection of original essays, the contributors look again at the great cataclysm of that monumental day -- December 7, from the American perspective; December 8 on the other side of the International Date Line -- to assess its impact from an angle different than usual. While not ignoring the strategic military meaning of the attacks or the domestic political impact of the attacks on the major belligerents, they focus on how Japan's great -- if short-lived -- victories roiled the Pacific world. Collectively, they analyze the impact of the attacks Japan launched that day -- on O'ahu, of course, but also on the Philippines, Malaya, Guam, Wake Island, Hong Kong, Singapore, and Thailand. These attacks and their aftermath, if seen as interconnected, expose broader historical patterns. They reveal the arc of imperialism, colonialism, and burgeoning nationalism in the Pacific world; they demonstrate the transformation of racial solidarities and racial identities within and across Pacific world societies; and they show how a variety of elite actors incorporated the attacks into new regimes of knowledge and expertise that challenged and displaced prior disciplinary hierarchies. In the contributors' analysis, the attacks of December 7/8 belong to a story of clashing empires and anti-colonial visions -- a story told from multiple perspectives"--